PERUBAHAN KEDUDUKAN KELURAHAN DARI PERANGKAT DAERAH MENJADI PERANGKAT KECAMATAN - Rauf, Rahyunir (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
Regional Government is a sub-system of the national government, the existence of local government has been established in Article 18 of the 1945 Constitution and Article 18 A and 18 B of the RI Constitution (Amendment). In Article 1 of the 1945 Constitution states that the State of Indonesia is a unitary state of the Republic. Logical consequence as a unitary state is the formation of the government of the State of Indonesia as a national government for the first time and then the national government for the first time and then the national government that then form the Region in accordance with the provisions of legislation. Then Article 18 Paragraph (2) and Paragraph (5) of the 1945 Constitution states that the regional government has the authority to regulate and manage its own Governmental Affairs according to the Autonomy and Co-Administration Principles and is given the widest autonomy. Along with the development and dynamics in the field Especially the regional government, the government issued Law No. 23 of 2014 on Regional Government in lieu of Law Number 32 Year 2004 on Regional Government. In helping to carry out the concurrent affairs and general government affairs, the Head of Regency / Municipality is assisted by the area. In the juridical existence of the regional apparatus there is a change between Law Number 23 Year 2014 with Law Number 32 Year 2004, so far sub-district and kelurahan institutions become part of the regional apparatus of regency / city, so that directly Camat and Lurah are responsible to the Regent / Mayor. However, in Law No. 23 of 2014 there is a change of position of Kelurahan which has been putting kelurahan as a regional tool but nowadays become a subdistrict apparatus, consequently the Head of Village is no longer responsible to the Regent / Mayor but is directly responsible to the Camat. Therefore, the structure, system, guidance and accountability of the village administration changed